Modeling nonlinear systems using multiple piecewise linear equations - Lowe, G. K. K.; Zohdy, M. A. A. (Nonlinear Analysis: Modelling and Control, 2010)
This paper describes a technique for modeling nonlinear systems using multiple piecewise linear equations. The technique provides a means for linearizing the nonlinear system in such a way as to not limit the large signal behavior of the target system. The nonlinearity in the target system must be able to be represented as a piecewise linear function. A simple third order nonlinear system is used to demonstrate the technique. The behavior of the modeled system is compared to the behavior of the nonlinear system.